Pengaruh Bahan Ajar Kimia Berbasis Nilai Spiritual terhadap Hasil Belajar dan Minat Siswa Ditinjau dari Kemampuan Awal - Ayu Murtia Br Tarigan; Ayi Darmana (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the influence of chemistry teaching materials that integrate spiritual values on learning outcomes, learning interests, and students' spiritual attitudes, as well as the influence of initial abilities and the interaction of the two on learning outcomes. This study uses a pseudo-experiment method with a two-group pretest-posttest design. The research sample was determined through purposive sampling techniques, namely class XI P1 as an experimental class, and class XI P3 as a control class at SMA Negeri 1 Sei Bingai. The research instrument consisted of learning outcome tests, learning interest questionnaires, and spiritual attitude questionnaires that have been validated and declared reliable. Data analysis was carried out using the two-way ANOVA test, independent sample t-test, and paired sample t-test at a significance level of 0.05. The results of the study show that chemistry teaching materials that are integrated with spiritual values have a significant effect on learning outcomes, learning interests, and spiritual attitudes of students. In addition, initial ability also has a significant effect on learning outcomes, but there is no interaction between teaching materials and initial ability on student learning outcomes. These findings confirm that integrating spiritual values in chemistry teaching materials can not only improve learning outcomes, but also strengthen students' spiritual character.